Evaluation of disability in Carson McCullers' The Ballad of the Sad Café - Kocsoy, F. Gul (My University, 2021)
This study enquires into Carson McCullers' The Ballad of the Sad Café (1951) in terms of Disability Studies. McCullers problematizes the disabled body as ‘the other/marginalized’ by introducing a disabled/freak character, Cousin Lymon, who is a hunchbacked dwarf and an outcast; he is mischievous, talkative and intriguer. Thus, she opens questions about the characterization of disabled people employing a setting of the gothic/grotesque American south where people are prejudiced against the disabled. At the beginning, Lymon is pitiful/pitied, desires to be liked and socially accepted. Later, he asserts his personality, benefits from his vulnerability and proves his multi-dimensional and manipulative character. He takes advantage of Miss Amelia’s attraction to him. He is not a role model, moreover, he is an evil force and a grotesque figure. He abandons her for the sake of her enemy, her husband, whom she dismissed from her house long before. He invalidates her reliance on him and leaves her alone. He sets everybody in the neighborhood aback, because she had helped him in his most needy time. In this way, McCullers de/reconstructs the prejudice and stereotyping against disabled people, seeming to confirm the southern point of view. She blurs the line between the concepts and perceptions of disability and non-disability.
Keywords: The Ballad of the Sad Café; disability studies; American south; Carson McCullers; grotesque